2004
DOI: 10.1177/1055329003252057
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice About AIDS and Condom Utilization Among Health Workers in Rwanda

Abstract: Health workers in rural Rwanda were surveyed cross-sectionally on knowledge, attitude, and practice (KAP) about AIDS, HIV, and condom utilization. Participants were 350 health workers from six randomly chosen communities (three rural, three semirural). In general, knowledge about HIV/AIDS was moderate to good, with an average of 63% of the questions answered correctly; men (and younger respondents) had a better knowledge than did women (p =.01; older participants, p =.015). However, in the specific area of HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 8 publications
1
34
1
Order By: Relevance
“…In some studies, the level of knowledge was higher among men and young people. 40 There was a difference between occupational groups in terms of knowledge and attitude levels; physicians had higher scores of knowledge and attitude. The physicians in our study had higher scores on condom use, HIV diagnosis and clinical progression of AIDS compared to other occupations.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, the level of knowledge was higher among men and young people. 40 There was a difference between occupational groups in terms of knowledge and attitude levels; physicians had higher scores of knowledge and attitude. The physicians in our study had higher scores on condom use, HIV diagnosis and clinical progression of AIDS compared to other occupations.…”
Section: Discussionmentioning
confidence: 99%
“…Health workers also are potential role models and sources of reliable HIV information for their relatives, friends, and neighbors because they are respected for their health knowledge (Rahlenbeck, 2004; Talashek et al, 2007; Tarwireyi & Majoko, 2003). Even health facility workers like guards and cooks, who are not directly involved in patient care, are often asked questions about HIV by their relatives and neighbors.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-documented that health workers in African countries continue to have inadequate HIV prevention knowledge, stigmatizing attitudes, and risky personal behaviors (Adebajo, Bamgbala, & Oyediran, 2003; Dieleman et al, 2007; Ezedinachi et al, 2002; Rahlenbeck, 2004; Walusimbi & Okonsky, 2004). At least one study reported that more-educated workers had fewer knowledge deficits (Walusimbi & Okonsky, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they reported that one third of the providers were uncomfortable informing women of their HIV status and providing advice to them (Creek et al, 2004). Another study conducted among 350 health care workers in rural Rwanda led researchers to conclude that, based on participants' knowledge and attitudes, there is an urgent need for educational programs for health care workers (Rahlenbeck, 2004). Walusimbi and Okonsky (2004) studied knowledge and attitudes about HIV among nurses and midwives who worked in the major teaching hospital in Kampala.…”
mentioning
confidence: 99%